2012
DOI: 10.1111/j.1432-2277.2012.01544.x
|View full text |Cite
|
Sign up to set email alerts
|

IVIG and rituximab for treatment of chronic antibody-mediated rejection: a prospective study in paediatric renal transplantation with a 2-year follow-up

Abstract: Summary Chronic antibody‐mediated rejection (AMR) is the major cause of late renal allograft loss. There is, however, no established treatment for this condition. We report the results of a prospective pilot study on an antihumoral therapy (AHT) consisting of high‐dose intravenous immunoglobulin G (IVIG) and rituximab in 20 paediatric renal transplant recipients. Donor‐specific HLA antibodies (HLA DSA) were quantified by Luminex‐based bead array technology. Loss of eGFR decreased significantly from 7.6 ml/min/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 33 publications
4
65
2
2
Order By: Relevance
“…Fig. 3 Algorithm for diagnosis and treatment of chronic antibody-mediated rejection according to Billing et al [63] CAMR is the main cause of long-term graft loss. The diagnosis with transplant glomerulopathy and/or transplant vasculopathy as criteria is straightforward.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 3 Algorithm for diagnosis and treatment of chronic antibody-mediated rejection according to Billing et al [63] CAMR is the main cause of long-term graft loss. The diagnosis with transplant glomerulopathy and/or transplant vasculopathy as criteria is straightforward.…”
Section: Resultsmentioning
confidence: 99%
“…In a larger trial with 20 patients and a 2-year follow-up, the researchers confirmed that the decrease of GFR could be significantly reduced over 2 years by this combination treatment, and the response rate was 70 %. This result was associated with a 61 % decrease in HLA class I antibodies and a 63 % decrease in HLA class II antibodies [63]. A study in adults showed that a combination of this regimen with plasmapheresis therapy can further improve these results [64].…”
Section: Chronic Antibody-mediated Rejection (Camr)mentioning
confidence: 99%
“…In a pediatric study by Billing et al [34], all 20 children with CAMR had proteinuria and 35 % of them had nephrotic-range proteinuria. Based on the results of these studies, transplant glomerulopathy would appear to be a negative prognostic factor for both proteinuria and graft loss.…”
Section: Rejectionmentioning
confidence: 99%
“…Anti-HLA Class II antibodies reported to be strongly related to development of TG in a large cohort of kidney transplant recipients (8). Regarding the chronic AMR, the presence of transplant glomerulopathy has been shown to be inversely correlated with allograft survival and treatment response (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there are no well-established guidelines or approved treatment for chronic AMR, recently a numerous of studies have been published about the influence of rituximab (a monoclonal anti-CD 20 antibody) alone or combination with intravenous immunoglobulin G (IVIG) on progression and outcomes of chronic AMR with inconsistent results (4,(9)(10)(11)(12)(13). These studies were mostly retrospective, and have distinct inclusion criteria and end points for evaluation of response.…”
Section: Introductionmentioning
confidence: 99%